2021
DOI: 10.1111/pbi.13674
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of gene loss propensity in the pangenomes of three Brassica species suggests different mechanisms between polyploids and diploids

Abstract: Summary Plant genomes demonstrate significant presence/absence variation (PAV) within a species; however, the factors that lead to this variation have not been studied systematically in Brassica across diploids and polyploids. Here, we developed pangenomes of polyploid Brassica napus and its two diploid progenitor genomes B. rapa and B. oleracea to infer how PAV may differ between diploids and polyploids. Modelling of gene loss suggests that loss propensity is primarily associated with transposable elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 86 publications
(160 reference statements)
1
48
0
6
Order By: Relevance
“…These barley PAV tags will help construct future barley pangenomes and can be applied to association analysis. Pangenomics ML has also been applied to understand gene loss mechanisms in Brassica [ 134 ]. It was demonstrated that gene loss was mainly associated with transposable elements in the diploid B. oleracea and B. rapa, while in the polyploid B. napus, the loss of genes was mostly associated with homoeologous recombination.…”
Section: The Breeding Potential Of Under-utilised Crop Speciesmentioning
confidence: 99%
“…These barley PAV tags will help construct future barley pangenomes and can be applied to association analysis. Pangenomics ML has also been applied to understand gene loss mechanisms in Brassica [ 134 ]. It was demonstrated that gene loss was mainly associated with transposable elements in the diploid B. oleracea and B. rapa, while in the polyploid B. napus, the loss of genes was mostly associated with homoeologous recombination.…”
Section: The Breeding Potential Of Under-utilised Crop Speciesmentioning
confidence: 99%
“…The increasing availability of reference genome assemblies made it clear that there is significant presence/absence variation (PAV) between individuals (9)(10)(11)(12). This insight has led to the production of pangenomes that reflect the gene content of a species rather than an individual (10,(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability of reference genome assemblies made it clear that there is significant presence/absence variation (PAV) between individuals (912). This insight has led to the production of pangenomes that reflect the gene content of a species rather than an individual (10,1320). Pangenomes are now available for several plant species; the first bread what pangenome representing the gene content of 16 bread wheat cultivars was published in 2017 (18).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, homoeologous exchanges often underlie gene presence-absence variation and agronomically valuable quantitative trait loci in Brassica napus (Stein et al 2017;Samans et al 2017;Hurgobin et al 2017;Bayer et al 2021) and generate novel, chimeric transcripts in multiple polyploid species (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%